Progress in Carbon Nanotube-Based Electrochemical Biosensors–A Review. - Lawal, Abdulazeez Tunbosun; Bolarinwa, Hakeem Sanya; Adeoye, Moriam Dasola; Animasahun, Lukman O.; Alabi, Kazeem Adelani (My University, 2019)
The use of carbon nanotubes (CNT) for fabrication of sensors and biosensors has increased considerably over the past decade. This review covers the progress and advances made during the years (2014-2018) in the utilisation of carbon nanotubes for fabrication of electrochemical biosensors. The focus of the review is on reported CNT-based biosensors for detection of, important substances, such as glucose, H2O2, (DNA), ascorbic acid, uric acid, dopamine, metal ions, and pesticides. The review starts by first discussing the structures and properties of CNTs, followed by discussion of some of the synthetic methods for CNTs preparation. The working principles and performances of CNT-based biosensors are then discussed. Considerations for future developments in CNT-based biosensors are also outlined.
Keywords: Biosensors; Carbon nanotube; Functionalisation; Glucose; Nanomaterials